Community-Based Islamic Philanthropy in Strengthening the Resilience of Muslim Muallaf in the Belu Border Area, NTT - M Usman; Roykhatun Nikmah; Putu Widhi Iswari (Jurnal Al-Hakim: Jurnal Ilmiah Mahasiswa, Studi Syariah, Hukum dan Filantropi, 2026)
This study analyzes the contribution of community-based Islamic philanthropy to strengthening the resilience of Muslim muallaf families in the Belu border area, NTT. Muallaf families in this region face multiple challenges, including economic hardship, adaptation to a new religious identity, and social vulnerability as a minority group. In this context, recitation communities play an important role in implementing Islamic philanthropic practices based on socio-religious solidarity to support the sustainability of Muslim family life. This study employs a qualitative field study with a sociological approach. Data were collected through interviews, observations, and documentation involving muallaf families, religious leaders, and Muslim worshippers in Belu, NTT. The data were analyzed descriptively and analytically to identify forms of Islamic philanthropic practices and their contribution to family resilience. The findings reveal that Islamic philanthropy is distributed in both material and non-material forms through consumptive-traditional and consumptive-creative patterns. Based on Froma Walsh’s framework of family resilience, philanthropy contributes positively to the belief-system dimension by fostering acceptance and optimism among muallaf families as they cope with social and economic pressures. However, in the family organization dimension, philanthropic assistance has not fully fostered flexibility or long-term improvement in family resilience, as most practices remain charitable and short-term rather than empowerment-oriented. In the aspect of social support and communication, regular religious mentoring has strengthened family resilience. The study highlights the need to transform Islamic philanthropy from consumptive charity into sustainable, productive empowerment for muallaf families in border areas.